An outbreak of COVID-19 associated with a fitness centre in Saskatchewan: Lessons for prevention - Maureen Anderson (Public Health Agency of Canada, 2021)
Background: An outbreak of the coronavirus disease 2019 (COVID-19) occurred in Saskatchewan from September 12 to October 20, 2020. The index event, attendance at a local gym, seeded six additional clusters/outbreaks in multiple settings. These included a high school, a hospital, three workplaces (A, B and C) and several households. The overall cluster comprised 63 cases, 27 gym members and an additional 36 second, third and fourth generation cases.